Aging-related changes in the thiol/disulfide redox state: implications for the use of thiol antioxidants - Dröge, Wulf (Experimental gerontology, 2002)
Genetic and biochemical studies suggest that free radical-derived reactive oxygen species play a key role in a common mechanism of aging in many or all animal species. This led to the hypothesis that the quality of life in old age may be improved by pharmacological or dietary thiol antioxidants. This review describes important details about how the organism deals with its own thiol antioxidants. Aging was found to be associated with an oxidative shift in the thiol/disulfide redox state (REDST) of the intracellular glutathione pool and of the plasma cyst(e)ine and albumin pools. There is also a decrease in plasma thiol (mainly cysteine) concentration. The oxidative shift in intracellular REDST was found to be typically associated with cellular dysfunctions. Studies in humans related to plasma REDST revealed correlations with aging-related pathophysiological processes, suggesting that oxidative changes in REDST play a key role in processes and diseases which limit the human life span. The age-related shift in plasma REDST is mediated, at least partly, by the decreasing capacity to remove dietary cysteine from the oxidative environment of the blood. Thiol antioxidants were found to ameliorate various aging-related processes but obviously ought to be used with caution in consideration of the oxidative environment of the blood.
Gesehen am 03.02.2021